2011
DOI: 10.1007/s00103-011-1358-2
|View full text |Cite
|
Sign up to set email alerts
|

Warum rauchen Mütter?

Abstract: Using a cross-sectional population sample of 3,129 women with minor children, this paper analyzes the impact of social and psychological factors on maternal smoking. Pearson's χ(2) was used for testing significance of differences between smoking prevalence and social as well as psychological factors. Adjusted effects of these factors were calculated by means of multiple logistic regression analysis. About 30% of mothers smoked daily and about 11% were heavy smokers ( ≥ 20 cigarettes/day). Lower educational deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
1
0
2
Order By: Relevance
“…Single mothers are considered according to some studies as a socially disadvantaged group with higher risks of poverty and ill-health than other women [ 44 ]. Despite the increasing protective behaviour towards children’s exposure to SHS over time for both single and non-single mothers, in accordance with other studies [ 45 , 46 ], after a descriptive analysis for our data, we observed that single mothers are more likely to expose their children to SHS at home than non-single mothers. As implementing the smoking ban does not show an increasing risk of exposing children of single mothers to domestic SHS, the smoking ban can be integrated with targeted campaigns raising awareness and improving the social environment of single mothers to reduce the relative high exposure of children of this social category to SHS [ 46 ].…”
Section: Discussionsupporting
confidence: 92%
“…Single mothers are considered according to some studies as a socially disadvantaged group with higher risks of poverty and ill-health than other women [ 44 ]. Despite the increasing protective behaviour towards children’s exposure to SHS over time for both single and non-single mothers, in accordance with other studies [ 45 , 46 ], after a descriptive analysis for our data, we observed that single mothers are more likely to expose their children to SHS at home than non-single mothers. As implementing the smoking ban does not show an increasing risk of exposing children of single mothers to domestic SHS, the smoking ban can be integrated with targeted campaigns raising awareness and improving the social environment of single mothers to reduce the relative high exposure of children of this social category to SHS [ 46 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, these are often children of single parents (usually mothers). Since it is known from literature that an above-average number of single parents are smokers [ 70 72 ], we conducted additional analyses in which the family type was taken into account (results not shown). In line with current research, these revealed that the 0- to 6-year-old children of single parents are more frequently exposed to SHS at home than peers who live in two-parent families (KiGGS baseline study: 44.5 vs. 22.0 %; KiGGS Wave 1: 13.4 vs. 5.9 %).…”
Section: Discussionmentioning
confidence: 99%
“…Für die Zielgruppe der Mütter wurden bei täglichem Tabakkonsum ein niedriger sozialer Status, alleinige Erziehungsverantwortung und die Geburt des ersten Kindes vor dem 21. Lebensjahr als Risikofaktoren identifiziert 11 12 . Bei gelegentlichem Tabakkonsum zeigen sich hingegen keine signifikanten Unterschiede in Abhängigkeit vom sozialen Status.…”
Section: Rauchverhalten Und Strategien Zum Rauchstopp Vor Und Nach Der Geburtunclassified
“…Bei gelegentlichem Tabakkonsum zeigen sich hingegen keine signifikanten Unterschiede in Abhängigkeit vom sozialen Status. In Bezug auf psychische Faktoren zeigen rauchende Mütter häufiger eine substanzmittelorientierte Stressbewältigungsstrategie, setzen den Tabakkonsum also gezielt zur Stressreduktion ein 11 .…”
Section: Rauchverhalten Und Strategien Zum Rauchstopp Vor Und Nach Der Geburtunclassified